Xiaoxuming decoction cutting formula reduces LPS-stimulated inflammation in BV-2 cells by regulating miR-9-5p in microglia exosomes - Wang, Menglei; Yang, Yuting; Guo, Yanlei; Tan, Ruirong; Sheng, Yanmei; Chui, Huawei; Chen, Ping; Luo, Hua; Ying, Zhujun; Li, Li; Zeng, Jin; Zhao, Junning (Frontiers in Pharmacology, 2023)
The Background: Stroke is one of the leading causes of morbidity and mortality, and the inflammatory mechanism plays a crucial role in stroke-related brain injury and post-ischemic tissue damage. Xiaoxuming decoction (XXMD) is the first prescription for the treatment of “zhongfeng” (a broad concept referring to stroke) in the Tang and Song Dynasties of China and has a significant position in the history of stroke treatment. Through the study of ancient medical records and modern clinical evidence, it is evident that XXMD has significant efficacy in the treatment of stroke and its sequelae, and its pharmacological mechanism may be related to post-stroke inflammation. However, XXMD contains 12 medicinal herbs with complex composition, and therefore, a simplified version of XXMD, called Xiaoxuming decoction cutting (XXMD-C), was derived based on the anti-inflammatory effects of the individual herbs. Therefore, it is necessary to explore and confirm the anti-inflammatory mechanism of XXMD-C. Aim of the study: Based on the previous experiments of our research group, it was found that both XXMD and XXMD-C have anti-inflammatory effects on LPS-induced microglia, and XXMD-C has a better anti-inflammatory effect. Since miRNAs in exosomes also participate in the occurrence and development of cardiovascular diseases, and traditional Chinese medicine can regulate exosomal miRNAs through intervention, this study aims to explore the anti-inflammatory mechanism of XXMD-C in the treatment of post-stroke inflammation through transcriptome sequencing, providing a basis for the application of XXMD-C. Materials and methods: XXMD-C was extracted using water and filtered through a 0.22 μm membrane filter. The main chemical components of the medicinal herbs in XXMD-C were rapidly qualitatively analyzed using ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS). Cell viability was determined using the CCK-8 assay, and an LPS-induced BV-2 cell inflammation model was established. The expression of inflammatory cytokines was detected using ELISA and Western blot (WB). Extracellular vesicles were extracted using ultracentrifugation, and identified using transmission electron microscopy (TEM), nanoparticle tracking analysis, and WB. Differential miRNAs were screened using smallRNA-seq sequencing, and validated using RT-PCR and Western blot. Results: The UPLC-Q-TOF-MS analysis revealed that representative components including ephedrine, pseudoephedrine, cinnamaldehyde, baicalin, baicalein, wogonin, and ginsenoside Rg1 were detected in XXMD-C. The results of ELISA and WB assays showed that XXMD-C had a therapeutic effect on LPS-induced inflammation in BV-2 cells. TEM, nanoparticle tracking analysis, and WB results demonstrated the successful extraction of extracellular vesicles using high-speed centrifugation. Differential miRNA analysis by smallRNA-seq identified miR-9-5p, which was validated by RT-PCR and WB. Inhibition of miR-9-5p was found to downregulate the expression of inflammatory factors including IL-1β, IL-6, iNOS, and TNF-α. Conclusion: The study found that XXMD-C has anti-neuroinflammatory effects. Through smallRNA-seq sequencing of extracellular vesicles, miR-9-5p was identified as a key miRNA in the mechanism of XXMD-C for treating neuroinflammation, and its in vivo anti-inflammatory mechanism deserves further investigation.